Propuesta de mejora al modelo de investigación de la universidad EAN como herramienta de competitividad (2013)
This paper shows the analysis of the importance of research in higher education as a competitive tool, based on the origins of the academy in the world, and analyzing the characteristics of the most prominent universities in the research area given the variables Iberoamerican ranking qualified SIR ​​2013, and finally generating a proposal to improve the model of university research EAN considering and effective models developed in other countries and Latin American universities